Femtosecond Laser Micro Milling Using Special Trepanning Optics: Ultrafast lasers combined with trepanning optics enable new options for micromachining. Issue 2 (12th April 2017) - Friedel, Susanna; Stolberg, Klaus
Abstract: Micromachining methods like electrical discharge machining (micro‐EDM), chemical etching, mechanical micro milling or thermal laser machining, are limited by material properties like chemical reactivity, optical absorption, electrical conductivity, and melting point. Also, the demand for a wall steepness of 90°, a feature size of < 100 μm, radius of curvature < 20 μm, or the required process speed limit the choice of the appropriate technology. Here, the combination of ultrafast lasers with a special optical setup enables new solutions.